THE EFFECT OF TALENT MANAGEMENT ON EMPLOYEE ENGAGEMENT AND EMPLOYEE RETENTION IN IMPROVING EMPLOYEE PERFORMANCE - Fahma Diena Achmada; Budi Eko Soetjipto; Sopiah (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
Employee performance is an essential factor for company success. Optimal employee performance will affect the company's development in producing good products. This study aims to determine the application of Talent Management to Employee Engagement and Employee Retention in Improving Employee Performance at PT XYZ Surabaya employees. This study's population was PT XYZ Surabaya employees, totaling 393 people. The sampling technique uses the slovin formula with an error tolerance of 5%, and the sample used in this study is 200 employees. The data analysis technique in this study is as follows PLS-SEM analysis using SmartPLS software. The results showed that: 1) Talent management has a positive and significant direct effect on employee engagement, 2) Talent management has a positive and significant direct effect on employee retention, 3) Talent management has a positive and significant direct effect on employee performance, 4) Employee engagement has no direct positive and significant effect on employee performance, 5) Employee retention has a positive and significant direct effect on employee performance, 6) Employee engagement has a positive and significant direct effect on employee retention, 7) Talent management has no direct effect on employee performance indirectly through employee engagement, and 8) Talent management influences employee performance indirectly through employee retention.